Intrapreneurship Tenaga Kependidikan Institut Bisnis Dan Informatika Kesatuan Bogor - Widya Widya; Mumuh Mulyana; Febry Lodwyk Rihe Riwoe; Saefudin Zuhdi (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2023)
The purpose of this study is to: (1) Determine the effect of Employee Intrapreneurship on Emphaty, (2) Determine the effect of Employee Intrapreneurship on Reliability, and (3) Determine the effect of Employee Intrapreneurship on Responsiveness. (4) Determine the effect of Employee Intrapreneurship on Tangible and (5) Determine the effect of Employee Intrapreneurship on Assurance. The number of sample used that were used is 130 responses, using the formula Hair et al. To Determine the effect of Employee Intrapreneurship on service performance Institut Bisnis and Informatika Kesatuan Bogor, the data analysis method used is SEMPLS. Data collection was carried out using SmartPLS 4.0. According to the study's results, the following information was obtained: (1) There is positive evidence that Intrapreneurship Karyawan is related to Emphaty. (2) There is a significant positive effect of Employee Intrapreneurship on Reliability, (3) there is a significant positive effect of Employee Intrapreneurship on Responsiveness, (4) there is a significant positive effect of Employee Intrapreneurship on Tangible, (5) there is a significant positive effect of Employee Intrapreneurship on Assurance. Keywords: Intrapreneurship Karyawan, Emphaty, Reliability, Responsiveness, Tangible, Assurance